Positive electrode active material and method for producing same
Patent Information
- Application Number
- JP2024546324
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-05-22
AI Technical Summary
【0024】 本発明の正極活物質は、単粒子形態のリチウム遷移金属酸化物を含む単粒子型正極活物質として、結晶粒子内の境界面のうち強い境界にのみコバルトを含むコーティング部が形成されており、高い電極密度を有し、且つ優れた寿命特性および出力特性を発揮することができる。
Smart Images

Figure 2025505635000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0062248 filed on May 20, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a positive electrode active material and a method for producing the same. [Background technology]
[0003] Recently, with the development of technologies such as electric vehicles, the demand for high-capacity secondary batteries is increasing. Accordingly, research on positive electrodes using high nickel (High Ni) positive electrode active materials with excellent capacity characteristics is being actively conducted.
[0004] The high-nickel positive electrode active material is manufactured by co-precipitation, and the manufactured high-nickel positive electrode active material has the form of secondary particles formed by aggregation of primary particles. However, the active material having the form of secondary particles has the disadvantage that fine cracks occur in the secondary particles during a long-term charge / discharge process, causing side reactions, and when the density of the electrode is increased to improve the energy density, the secondary particles cause the structure to collapse, resulting in a decrease in the active material and electrolyte, resulting in a decrease in energy density and a decrease in life characteristics.
[0005] In order to solve the problems of such secondary particle-type high nickel positive electrode active materials, single particle type nickel-based positive electrode active materials have been developed recently. Single particle type nickel-based positive electrode active materials have the advantage that the particles do not collapse even when the density of the electrode is increased for high energy density. However, single particle type nickel-based positive electrode active materials require a relatively high sintering temperature to manufacture them, and the layered structure of R-3m is not properly maintained, and lithium is released from the crystal structure, causing a phase change to an Fm-3m rock-salt structure such as NiO, which reduces the crystallinity of the positive electrode active material, and the ratio of NiO increases on the surface of the manufactured single particle, and the increase in NiO increases resistance, resulting in a decrease in energy density and output. In addition, when the sintering temperature is low, there is a problem that the material exists in the form of over-sintered secondary particles, and the improvement effect on life and gas generation does not reach the level expected from single particles.
[0006] Therefore, there is still a need to develop a positive electrode active material that has high electrode density and exhibits excellent life and output characteristics. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] KR 2019-0094529 A1 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a positive electrode active material that has high electrode density and exhibits excellent life characteristics and output characteristics.
[0009] Another object of the present invention is to provide a method for producing a positive electrode active material having high electrode density and exhibiting excellent life characteristics and output characteristics. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention provides a positive electrode active material.
[0011] (1) The present invention provides a positive electrode active material comprising a single-particle lithium transition metal oxide and a coating portion containing cobalt formed on a surface of the single-particle lithium transition metal oxide, the single-particle lithium transition metal oxide comprising an interface that is divided into a strong interface where a layered structure is collapsed within a crystal particle and a weak interface where the layered structure is not collapsed, and the coating portion is formed only on the strong interface.
[0012] (2) The present invention provides a positive electrode active material according to the above (1), wherein the lithium transition metal oxide in a single particle form contains 2 to 50 crystal grains.
[0013] (3) The present invention provides a positive electrode active material according to the above (1) or (2), wherein the collapse of the layered structure of the strong boundaries is the collapse of the layered structure of the NiO layer.
[0014] (4) The present invention provides a positive electrode active material according to any one of the above (1) to (3), wherein the strong boundary exhibits a shading difference in an electron backscatter diffraction (EBSD) band contrast map and an Eular map, and the weak boundary exhibits no shading difference in an electron backscatter diffraction (EBSD) band contrast map but exhibits a shading difference in an Eular map.
[0015] (5) The present invention provides a positive electrode active material according to any one of (1) to (4) above, wherein the lithium transition metal oxide in the form of a single particle contains 10% or more of the strong boundaries based on the number of all boundary surfaces.
[0016] (6) The present invention provides a positive electrode active material according to any one of (1) to (5) above, wherein a strong boundary at which the cobalt coating layer is formed includes a nickel-cobalt-manganese oxide layered structure converted from a NiO layer.
[0017] (7) The present invention provides a positive electrode active material in any one of the above (1) to (6), wherein the cobalt coating layer formed at the strong boundary contains a composition of LiCoO2.
[0018] (8) The present invention provides a positive electrode active material according to any one of the above (1) to (7), wherein the lithium transition metal oxide is a lithium composite transition metal oxide containing nickel, cobalt, and manganese.
[0019] (9) The present invention provides a positive electrode active material in any one of the above (1) to (8), wherein the lithium transition metal oxide is a lithium composite transition metal oxide represented by the following chemical formula 1: [Chemical formula 1] Li a Ni x Co y M 1 z M 2 1-x-y-z O2 In the above Chemical Formula 1, M 1 is one or more selected from the group consisting of Mn and Al, 2 is one or more selected from the group consisting of B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, S, Sr, Ta, La, and Hf, and is 1.0≦a≦1.3, 0.6≦x<1.0, 0≦y≦0.4, and 0≦z≦0.4.
[0020] (10) The present invention provides a positive electrode active material according to any one of the above (1) to (9), wherein the lithium transition metal oxide is a lithium composite transition metal oxide represented by the following chemical formula 2: [Chemical formula 2] Li a Ni b Co cMn d M 1 e O2 In the above Chemical Formula 2, M 1 is at least one selected from the group consisting of Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S, and 0.9≦a≦1.1, 0.8≦b<1, 0 <c<0.2、0<d<0.2、0≦e<0.1、b+c+d+e=1である。 In order to achieve the above object, the present invention provides a method for producing a positive electrode active material.
[0021] (11) The present invention provides a method for producing a positive electrode active material, comprising the steps of: 1) mixing lithium transition metal oxide particles in a single particle form and a cobalt source; and 2) heat-treating the mixture of step 1).
[0022] (12) The present invention provides the method for producing a positive electrode active material according to (11), further comprising mixing an additional metal source in the step 1).
[0023] (13) The present invention provides a method for producing a positive electrode active material according to (11) or (12), wherein the heat treatment in step 2) is carried out at 500 to 800°C. Effect of the Invention
[0024] The positive electrode active material of the present invention is a single-particle type positive electrode active material containing a lithium transition metal oxide in a single-particle form, in which a coating portion containing cobalt is formed only on the strong boundaries among the boundaries within the crystal particles, and has high electrode density and can exhibit excellent life characteristics and output characteristics. [Brief description of the drawings]
[0025] [Figure 1] 1A is an EBSD band contrast map for the positive electrode active material of Example 1, FIG. 1B is an EPMA cobalt element map, and FIG. 1C is an Euler map. [Diagram 2] 1 is an EPMA cobalt element map of Comparative Example 1. [Diagram 3] 1A is an EBSD band contrast map for the positive electrode active material of Comparative Example 3, FIG. 1B is an EPMA cobalt element map, and FIG. 1C is an Euler map. [Figure 4] 1 is a SEM photograph of the positive electrode active material of Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will now be described in further detail in order to facilitate understanding of the present invention.
[0027] The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0028] In the present invention, the term "primary particle" refers to the smallest particle unit that can be distinguished as a single mass when a cross section of a positive electrode active material is observed through a scanning electron microscope (SEM), and may be composed of a plurality of crystal grains.
[0029] In the present invention, the term "secondary particle" refers to a secondary structure formed by aggregation of a plurality of primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer.
[0030] In the present invention, the term "single particle type" may be used instead of the term "single particle form", and refers to a form that is in contrast to the form of secondary particles formed by agglomeration of hundreds of primary particles produced by conventional methods. In addition, in the present invention, the term "single particle type positive electrode active material" or "lithium transition metal oxide in a single particle form" refers to a concept in contrast to a positive electrode active material in a form of secondary particles formed by agglomeration of hundreds of primary particles produced by conventional methods, and refers to a positive electrode active material or lithium transition metal active material consisting of 1 to 50 particles or less, 1 to 40 particles or less, 1 to 30 particles or less, 1 to 20 particles or less, 1 to 15 particles or less, 1 to 10 particles or less, or 1 to 5 particles or less.
[0031] In the present invention, the term "monocrystalline" may be used instead of the term "single crystal" and refers to a positive electrode active material or lithium transition metal oxide containing 2 to 50, specifically 2 to 30, crystal grains. Generally, a single crystal particle refers to a particle in which the entire sample is composed of only one grain or grain region. In the present invention, a single-particle type positive electrode active material or a single-particle type lithium transition metal oxide contains a small number of crystal grains and therefore can exhibit properties similar to those of a single crystal grain.
[0032] The term "single particle" refers to the smallest unit of a particle that can be recognized when observing a positive electrode active material through a scanning electron microscope, and the term "grain" or "grain region" refers to a region in which atoms in a sample are arranged continuously and periodically in one direction. The grains can be analyzed using an electron backscatter diffraction (ESBD) analyzer.
[0033] In the present invention, the term "average particle size (D 50The "average particle size" refers to the particle size at the 50% point of the cumulative volume distribution by particle size. The average particle size is determined by dispersing the powder to be measured in a dispersion medium, introducing it into a commercially available laser diffraction particle size measuring device (e.g., S3500 manufactured by Microtrac), measuring the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam, calculating the particle size distribution, and calculating the particle diameter at the 50% point of the cumulative volume distribution by particle size in the measuring device. 50 can be measured.
[0034] The positive electrode active material of the present invention comprises a lithium transition metal oxide in the form of a single particle, and a coating portion containing cobalt formed on the surface of the lithium transition metal oxide in the form of a single particle. The lithium transition metal oxide in the form of a single particle comprises an interface that is divided into a strong interface where a layered structure is collapsed within a crystal particle and a weak interface where the layered structure is not collapsed, and the coating portion is formed only on the strong interface.
[0035] In one embodiment of the present invention, the interface may be a surface where any single particle included in the single-particle-form lithium transition metal oxide contacts another single particle, a surface where any crystal grain contacts another crystal grain, or an interface formed by all of these.
[0036] The interface or boundary can be divided into a strong boundary where the layer structure of the transition metal oxide layer is broken and a weak boundary where the layer structure is not broken. The strong boundary can be confirmed by showing a shading difference in an electron backscatter diffraction (EBSD) band contrast map (BC map) and an Eular map (IPF map), and the weak boundary can be confirmed by showing a shading difference in an electron backscatter diffraction (EBSD) band contrast map and a shading difference in an Eular map. For example, in an Eular map, a single crystal domain is measured in the same color, so that each crystal domain can be distinguished, but in an electron backscatter diffraction (EBSD) band contrast map, since the crystallinity is divided, only the part where the atomic structure of the grain is broken can be measured, and only the strong boundary where the atomic structure is broken, i.e., the layer structure of the transition metal oxide layer is broken, can be measured.
[0037] The single particle lithium transition metal oxide may include the strong boundaries in an amount of 10% or more, specifically 10% to 80%, more specifically 20% to 60% of the total number of boundaries. The strong boundaries are boundaries where the layered structure of the transition metal oxide layer, particularly the layered structure of the NiO layer, is destroyed, and may cause cation mixing and structural instability, which may cause problems such as increased resistance, reduced capacity, and reduced output.
[0038] In the lithium transition metal oxide in the form of a single particle according to the present invention, the coating portion is formed only at the strong boundary at the boundary surface, and the coating portion is not formed at the weak boundary among the boundaries. When cobalt (Co) diffuses into the surface and interface of the lithium transition metal oxide in the form of a single particle, the strong boundary where the layer structure collapses is coated with cobalt, and the diffusion coating of cobalt is minimized at the weak boundary where the layer structure does not collapse, and a coating portion containing cobalt is not formed.
[0039] The lithium transition metal oxide in the form of a single particle of the present invention is coated with cobalt at the strong boundary, i.e., the boundary surface where the layer structure is collapsed, so that the collapsed layer of the layer structure is not exposed to the surface. The cobalt coating converts the NiO layer where the layer structure at the strong boundary is collapsed into a nickel cobalt manganese (NCM) oxide layer structure, and exerts an effect of reducing the collapsed layer of the layer structure contained in the lithium transition metal oxide in the form of a single particle, so that the positive electrode active material including the same can exhibit excellent cell characteristics. In addition, since no cobalt coating layer is formed on the weak boundary where the layer structure is not collapsed, it is possible to prevent the unnecessary cobalt coating layer from acting as a resistor or causing a decrease in capacity.
[0040] According to an embodiment of the present invention, a positive electrode active material includes a lithium transition metal oxide having a single particle form and a coating portion including cobalt formed on a surface of the lithium transition metal oxide having a single particle form, and the coating portion may be formed at a strong boundary with the surface of the lithium transition metal oxide having a single particle form.
[0041] The surface of the lithium transition metal oxide in the form of a single particle may have a layered (R-3m) structure, and the lithium transition metal oxide in the form of a single particle may have a high NiO content on the surface or in a region close to the surface of the particle due to the formation of NiO induced by the high sintering temperature required during the preparation. The coating portion containing cobalt may be a layer formed as the cobalt diffuses from the surface of the lithium transition metal oxide in the form of a single particle toward the center, and the cobalt diffused during the formation of the coating portion may convert the NiO layer into a nickel cobalt manganese (NCM) oxide layered structure, thereby reducing and eliminating causes of increased resistance, decreased energy density, decreased output, etc., and exhibiting excellent electrochemical properties. The coating portion may include a composition of LiCoO2.
[0042] When the coating portion is formed on the surface of the lithium transition metal oxide in the form of a single particle, it may be formed on a part or all of the outer edge of the surface, and may be formed on 10% to 100% (area %) of the total area of the surface. Specifically, the coating portion may be formed on a part of the surface of the lithium transition metal oxide in the form of a single particle, and may be formed on 30% to 90% of the total area of the surface.
[0043] The coating portion may be formed in an island shape on the surface of the lithium transition metal oxide. The island shape refers to a shape formed discontinuously on the surface, that is, when the coating portion is formed on the surface of the lithium transition metal oxide in the form of a single particle, the coating portion may be partially dispersed and distributed.
[0044] In the positive electrode active material according to an embodiment of the present invention, the lithium transition metal oxide in the form of single particles may be a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn).
[0045] Specifically, the lithium transition metal oxide in the form of a single particle may be a lithium composite transition metal oxide represented by the following Chemical Formula 1.
[0046] [Chemical formula 1] Li a Ni x Co y M 1 z M 2 1-x-y-z O2
[0047] In the above Chemical Formula 1, M 1 is one or more selected from the group consisting of Mn and Al, 2 is one or more selected from the group consisting of B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, S, Sr, Ta, La, and Hf, and 0.9≦a≦1.3, 0.6≦x<1.0, 0≦y≦0.4, and 0≦z≦0.4.
[0048] The a represents the molar ratio of lithium in the lithium transition metal oxide and may be 1.0≦a≦1.3, specifically 1.0≦a≦1.25, and more specifically 1.0≦a≦1.20.
[0049] The x represents the molar ratio of nickel to the total transition metals, and may be 0.6≦x<1.0, specifically 0.6≦x≦0.99 or 0.70≦x≦0.99, and more specifically 0.8≦x≦0.95. When the nickel content satisfies the above range, excellent capacity characteristics can be achieved.
[0050] The y indicates the molar ratio of cobalt to all transition metals, and may be 0≦y≦0.40, specifically 0≦y≦0.35, and more specifically 0.01≦y≦0.30.
[0051] The z is the element M among all transition metals. 1 and can be 0≦z≦0.40, specifically 0≦z<0.35, and more specifically 0.01≦z≦0.30.
[0052] The 1-xyz is M among all transition metals. 2 and can be 0≦1−xyz≦0.4, specifically 0≦1−xyz≦0.35, and more specifically 0≦1−xyz≦0.30.
[0053] Specifically, the lithium transition metal oxide may be a lithium composite transition metal oxide represented by the following Chemical Formula 2.
[0054] [Chemical formula 2] Li a Ni b Co c Mn d M 1 e O2
[0055] In the above Chemical Formula 2, M 1is at least one selected from the group consisting of Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S, and 0.9≦a≦1.1, 0.8≦b<1, 0 <c<0.2、0<d<0.2、0≦e<0.1、b+c+d+e=1である。
[0056] Specifically, the lithium transition metal oxide may be a lithium composite transition metal oxide represented by the following Chemical Formula 3.
[0057] [Chemical formula 3] Li g Ni h Co i Mn j O2
[0058] In the above formula 3, 0.9≦g≦1.1, 0.8≦h<1, 0 <i<0.2、0<j<0.2、h+i+j=1である。
[0059] The positive electrode active material has an average particle size (D 50 Specifically, the average particle size (D 50 The positive electrode active material according to one embodiment of the present invention may have an average particle size (D 50 When the average particle size of the particles is within the above range, it can have advantages in terms of rolling ratio, electrode voids, etc., and when the average particle size is too small or too large compared to the above range, it can degrade performance in terms of electrode capacity, life characteristics, resistance, etc.
[0060] The present invention also provides a method for producing the positive electrode active material.
[0061] The positive electrode active material may be prepared by a method including the steps of: 1) mixing lithium transition metal oxide particles in a single particle form and a cobalt source; and 2) heat-treating the mixture of step 1).
[0062] In step 1), the cobalt source may be used in an amount of 0.1 mol% to 10 mol%, specifically 0.5 mol% to 5 mol%, and more specifically 1 mol% to 3 mol%, based on the positive electrode active material. If the cobalt source is used in an amount that is too small compared to the above range, a sufficient coating layer may not be formed on the strong boundaries contained in the lithium transition metal oxide particles, and if the cobalt source is used in an amount that is too large, an excessive cobalt coating may be formed or unreacted cobalt compounds may remain on the surface of the particles, resulting in defects such as increased resistance and decreased capacity.
[0063] In step 1), a process of further mixing an additional metal source may be performed. The additional metal source may be used together with the cobalt source to be coated on the strong boundary of the lithium transition metal oxide in the form of a single particle, or may be coated on one or more of the surface, strong boundary, and weak boundary of the lithium transition metal oxide in the form of a single particle. The coating formed by the additional metal source may be mixed with the cobalt coating layer formed by the cobalt source on the strong boundary included in the lithium transition metal oxide particles, or may be formed as a separate coating layer. The additional metal source may be formed in the form of a metal oxide, a lithium metal oxide, a cobalt metal oxide, or a lithium cobalt metal oxide.
[0064] The mixing in step 1) may be a dry mixing, for example, a powdered cobalt source material may be mixed with a lithium transition metal oxide in the form of a single particle without a solvent. Such a dry mixing may be a simple mixing process, and the simplification of the process may provide advantages of cost reduction and quality stabilization.
[0065] 2) In the step of heat-treating the mixture of step 1), a coating portion is formed as cobalt diffuses from the surface of the single-particle lithium transition metal oxide toward the center, and the coating portion is formed at a strong boundary of the single-particle lithium transition metal oxide. Also, when the coating portion is formed at the strong boundary, an island-shaped coating portion may be discontinuously formed on the surface of the lithium transition metal oxide. In a method for manufacturing a positive electrode active material according to an embodiment of the present invention, the single-particle lithium transition metal oxide particles and a cobalt (Co) source are dry-mixed and then heat-treated, so that the coating portion may be formed in an island shape.
[0066] The heat treatment in step 2) may be performed at 500°C to 800°C, specifically 600°C to 800°C, and more specifically 650°C to 750°C.
[0067] When the heat treatment temperature satisfies the above range, the cobalt of the cobalt coating present on the surface of the lithium transition metal oxide in the form of a single particle is properly diffused during the temperature rise process for the heat treatment, and the NiO degenerated layer at the strong boundary can be properly changed to a nickel cobalt manganese (NCM) oxide layer structure. When the heat treatment temperature of the step 2) is low, the cobalt coating is partially formed only on the surface of the lithium transition metal oxide in the form of a single particle, and the cobalt coating may not be properly formed at the strong boundary. When the heat treatment temperature of the step 2) is high, the cobalt is doped deeply inside the lithium transition metal oxide in the form of a single particle, and the cobalt coating may not be properly formed at the strong boundary.
[0068] The heat treatment in step 2) can be performed for 2 hours to 12 hours, specifically, for 2 hours to 9 hours, and more specifically, for 2 hours to 6 hours. When the heat treatment is performed within the above time range, excellent productivity can be exhibited and uniform firing can be performed.
[0069] The cobalt source may be a cobalt-containing oxide, hydroxide, oxyhydroxide, carbonate, sulfate, halide, sulfide, acetate, nitrate, carboxylate, or a combination thereof, and examples thereof include Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, and Co(SO4)2·7H2O. Any one or a mixture of two or more of these may be used, and specifically, Co(OH)2 may be used.
[0070] The additional metal source may be, for example, an oxide, hydroxide, oxyhydroxide, carbonate, sulfate, halide, sulfide, acetate, nitrate, carboxylate, or a combination thereof, containing one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Cr, Hf, Ta, La, Ba, Ce, Sn, Y, and S. Specifically, ZnO, Al2O3, Al(OH)3, AlSO4, AlCl3, Al-isopropoxide, AlNO3, TiO2, WO3, AlF, H2BO3, HBO2, H3BO3, H2B4O7, B2O3, C6H5B(OH)2, (C6H5O)3B, (CH3(CH2)3O)3B, C3H9B3O6, (C3H7O3)B, Li3WO4, (NH4) 10 W 12 O 41 5H2O, NH4H2PO4, etc., but are not limited to these.
[0071] The additional metal source may be used in an amount such that the additional metal is 100 ppm to 50,000 ppm, specifically 200 ppm to 10,000 ppm, based on the total number of moles of metal in the positive electrode active material. When the additional metal is included in this range, it is expected that the side reaction with the electrolyte can be effectively suppressed, and the electrochemical properties can be further improved.
[0072] In one embodiment of the present invention, the lithium transition metal oxide particles in the form of single particles may be prepared by mixing a transition metal oxide precursor and a lithium source material, performing primary firing, crushing the pre-fired product prepared by the primary firing, and then performing secondary firing.
[0073] According to yet another embodiment of the present invention, there is provided a positive electrode comprising the above positive electrode active material.
[0074] Specifically, the positive electrode includes a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the above-mentioned positive electrode active material.
[0075] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0076] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material described above.
[0077] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery to be constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can usually be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0078] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0079] The positive electrode can be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode can be manufactured by applying a composition for forming a positive electrode active material layer, which is manufactured by mixing or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling. Here, the types and contents of the positive electrode active material, binder, and conductive material are as described above.
[0080] The solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used may be sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.
[0081] As another method, the positive electrode can also be produced by casting the composition for forming a positive electrode active material layer on another support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.
[0082] According to yet another embodiment of the present invention, there is provided an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0083] The lithium secondary battery specifically includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the positive electrode is as described above. The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0084] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0085] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0086] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0087] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO x(0 < x < 2), metal oxides such as SnO2, vanadium oxides, and lithium vanadium oxides that can be doped and undoped with lithium; or composites containing the metallic compound and a carbonaceous material, such as Si-C composites or Sn-C composites, etc. Any one or a mixture of two or more of these can be used. Also, a thin film of metallic lithium may be used as the negative electrode active material. Further, as the carbon material, both low-crystalline carbon and high-crystalline carbon can be used. Representative examples of low-crystalline carbon are soft carbon and hard carbon, and representative examples of high-crystalline carbon are amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch derived cokes.
[0088] Also, the binder and the conductive material are as described above for the positive electrode.
[0089] As an example, the negative electrode active material layer is produced by applying and drying a negative electrode forming composition in which a negative electrode active material, and optionally a binder and a conductive material, are dispersed in a solvent on a negative electrode current collector, or by casting the negative electrode forming composition on another support and then laminating the film obtained by peeling the support from the negative electrode current collector on the negative electrode current collector.
[0090] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.
[0091] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0092] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0093] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethanol and isopropyl alcohol, nitriles such as R-CN (R is a C2-C20 straight-chain, branched or cyclic hydrocarbon group that can contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of the battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.
[0094] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0095] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, in order to improve the life characteristics of the battery, suppress the decrease in the capacity of the battery, and improve the discharge capacity of the battery. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0096] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0097] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0098] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0099] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0100] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a large number of battery cells. EXAMPLES
[0101] Working Example DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0102] Manufacturing Example 1 Positive electrode active material precursor [composition: Ni 0.95 Co 0.03 Mn 0.02 (OH)2, average particle size (D 50 The mixture was mixed with LiOH as a lithium source material in a molar ratio of 1:1.05, and subjected to primary firing at a temperature of 850°C for 9 hours in an oxygen atmosphere to produce a pre-fired product. The calcined product was crushed and then secondary calcined at 750° C. for 9 hours in an oxygen atmosphere to produce a lithium transition metal oxide in the form of single particles.
[0103] Manufacturing Example 2 Positive electrode active material precursor [composition: Ni 0.88 Co 0.03 Mn 0.09 (OH)2, average particle size (D 50 The mixture was mixed with LiOH as a lithium source material in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 880°C for 9 hours in an oxygen atmosphere to produce a pre-fired product. The pre-calcined product was crushed and then secondary-calcined at 750° C. for 9 hours in an oxygen atmosphere to produce a lithium transition metal oxide in the form of single particles.
[0104] Production Example 3 A lithium transition metal oxide in the form of a single particle was prepared in the same manner as in Preparation Example 1, except that the primary sintering temperature was changed to 820° C. instead of 850° C. in Preparation Example 1.
[0105] Production Example 4 Positive electrode active material precursor [composition: Ni 0.95 Co 0.03 Mn 0.02 (OH)2, average particle size (D 50 The lithium transition metal oxide was produced by mixing the lithium sintered body 100% with LiOH as a lithium source material in a molar ratio of 1:1.05 and calcining the mixture at 740° C. for 9 hours in an oxygen atmosphere.
[0106] Production Example 5 Positive electrode active material precursor (composition: Ni 0.88 Co 0.03 Mn 0.09 (OH)2, average particle size (D 50 ):3.5μm) was mixed with LiOH as a lithium source material in a molar ratio of 1:1.05, and calcined at a temperature of 800℃ for 9 hours in an oxygen atmosphere to produce lithium transition metal oxide.
[0107] Example 1 The lithium transition metal oxide in the form of single particles prepared in Preparation Example 1 and a powdered cobalt source Co(OH)2 (manufactured by HUAYOU COBALT) were mixed in a ratio of 98 mol % and 2 mol %.
[0108] The mixture was heat-treated at a temperature of 700° C. for 5 hours to obtain a cake-like positive electrode active material, which was then pulverized to produce a powder-like single-particle type positive electrode active material.
[0109] Example 2 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 1, except that the single particle type lithium transition metal oxide prepared in Preparation Example 2 was used instead of the single particle type lithium transition metal oxide prepared in Preparation Example 1.
[0110] Example 3 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 1, except that the single particle type lithium transition metal oxide prepared in Preparation Example 3 was used instead of the single particle type lithium transition metal oxide prepared in Preparation Example 1.
[0111] Example 4 A powdered single-particle type positive electrode active material was produced in the same manner as in Example 1, except that the heat treatment temperature of the mixture was changed to 600°C.
[0112] Comparative Example 1 The single particle type lithium transition metal oxide prepared in Preparation Example 1 was used as a single particle type positive electrode active material.
[0113] Comparative Example 2 The single particle type lithium transition metal oxide prepared in Preparation Example 2 was used as a single particle type positive electrode active material.
[0114] Comparative Example 3 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 1, except that the mixture was heat-treated at a temperature of 400°C.
[0115] Comparative Example 4 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 1, except that the mixture was heat-treated at a temperature of 900°C.
[0116] Comparative Example 5 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 2, except that the mixture was heat-treated at a temperature of 400°C.
[0117] Comparative Example 6 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 2, except that the mixture was heat-treated at a temperature of 900° C.
[0118] Comparative Example 7 A powdered positive electrode active material was prepared in the same manner as in Example 1, except that the lithium transition metal oxide prepared in Preparation Example 4 was used instead of the single particle lithium transition metal oxide prepared in Preparation Example 1.
[0119] Comparative Example 8 A powdered single particle type positive electrode active material was prepared in the same manner as in Example 1, except that the single particle type lithium transition metal oxide prepared in Preparation Example 5 was used instead of the single particle type lithium transition metal oxide prepared in Preparation Example 1.
[0120] Comparative Example 9 The single particle lithium transition metal oxide produced in Production Example 1 and a powdered cobalt source Co(OH)2 (manufactured by HUAYOU COBALT) were mixed in a ratio of 99.98 mol % and 0.02 mol %.
[0121] The mixture was heat-treated at 750° C. for 5 hours to obtain a cake-like positive electrode active material, which was then pulverized to produce a powder-like single-particle type positive electrode active material.
[0122] Experimental Example 1: Analysis of Positive Electrode Active Material Each of the powdered single-particle positive electrode active materials produced in Example 1 and Comparative Examples 1 and 3 was subjected to Ar ion milling for 2 hours using an ion milling system (HITACHI, IM5000) (accelerating voltage: 6 kV) to prepare a cross-sectional sample.
[0123] 1) For each cross-sectional sample of the powdered single-particle type positive electrode active material produced in Example 1 and Comparative Example 3, an EBSD band contrast map was created using a field emission scanning microscope (SEM, JEOL JSM-7900F) (accelerating voltage: 20 kV). AztecCrystal manufactured by OXFORD Instruments was used as the image processing-EBSD quantification analysis software.
[0124] 2) For each cross-sectional sample of the powdered single-particle type positive electrode active material produced in Example 1 and Comparative Examples 1 and 3, an EPMA cobalt element map was obtained using an electron probe microanalyzer (EPMA, JEOL JXA-8530F) (accelerating voltage: 15 kV).
[0125] 3) The cross-sections of the powdered single particle type positive electrode active material samples prepared in Example 1 and Comparative Example 3 were measured and analyzed using a scanning microscope (SEM, JEOL JSM-7900F) (accelerating voltage: 20 kV). Euler maps were created using AztecCrystal manufactured by OXFORD Instruments as image processing-EBSD quantification analysis software.
[0126] The results of Example 1 are shown in FIG. 1, Comparative Example 1 in FIG. 2, and Comparative Example 3 in FIG.
[0127] 4) Using a scanning electron microscope (SEM, JEOL JSM-7900F), SEM photographs were taken of the surface of the positive electrode active material prepared in Comparative Example 7. The results are shown in FIG.
[0128] FIG. 1 (a) shows an EBSD band contrast map for the positive electrode active material of Example 1, (b) shows an EPMA cobalt element map, and (c) shows an Euler map. Referring to FIG. 1, in the positive electrode active material of Example 1, three grains and two boundaries between the grains are observed from the Euler map (c). On the other hand, in the EBSD band contrast map (a), only two regions and one boundary between the regions are observed. The boundary observed in common from the EBSD band contrast map and the Euler map is a strong boundary, and the boundary not observed from the EBSD band contrast map but observable from the Euler map is a weak boundary. When checking the EPMA cobalt elemental map (b) above, a cobalt (Co) coating layer was observed only at the strong interface, and it was confirmed that when particulate lithium transition metal oxide and powdered cobalt source Co(OH)2 were mixed and sintered, cobalt formed a coating layer only at the strong interface.
[0129] As a result, it was confirmed that the lithium transition metal oxide produced by crushing the calcined product produced by primary firing and then secondary firing as in Preparation Example 1 was in a single particle form, and it was also confirmed that the positive electrode active material of Example 1 produced using this was in a single particle form. In addition, it was confirmed that the positive electrode active material of Example 1 included strong and weak boundaries within the lithium transition metal oxide crystal particles, and that a cobalt (Co) coating layer was formed on the strong boundaries, and that a cobalt (Co) coating layer was not formed on the weak boundaries.
[0130] Figure 2 shows an EPMA cobalt element map of Comparative Example 1. Comparative Example 1 uses the single particle lithium transition metal oxide prepared in Preparation Example 1 without an additional cobalt coating process, and referring to Figure 2, it can be seen that the positive electrode active material of Comparative Example 1 has cobalt (Co) uniformly distributed in the cross section of the positive electrode active material.
[0131] FIG. 3 (a) shows an EBSD band contrast map, (b) shows an EPMA cobalt element map, and (c) shows an Euler map for the positive electrode active material of Comparative Example 3. Referring to FIG. 3, in the Euler map (c), three grains and two boundaries between the grains are observed for the positive electrode active material of Comparative Example 3. Meanwhile, in the EBSD band contrast map (a), only two regions and one boundary between the regions are observed. The boundary observed in common in the EBSD band contrast map and the Euler map is a strong boundary, and the boundary not observed in the EBSD band contrast map but observable in the Euler map is a weak boundary. In Comparative Example 3, the lithium transition metal oxide in the form of a single particle prepared in Preparation Example 1 and the powdered cobalt source Co(OH)2 were mixed and heat-treated at 400° C., which is a relatively lower temperature than 700° C. in Example 1. From the EPMA cobalt element map of FIG. 3(b), it was found that in the positive electrode active material of Comparative Example 3, no cobalt (Co) coating was observed at either the strong or weak boundaries, and a cobalt coating layer was observed only on the surface of the positive electrode active material. It was also found that when the heat treatment temperature for firing during the formation of the cobalt coating layer was low, the cobalt coating layer was not properly formed on the strong boundary surface.
[0132] Fig. 4 shows an SEM photograph of the positive electrode active material of Comparative Example 7. Referring to Fig. 4, it can be seen that the positive electrode active material of Comparative Example 7 has a secondary particle form formed by agglomeration of 50 or more primary particles. As a result, it can be seen that the lithium transition metal oxide prepared by only one firing as in Preparation Example 4 shows a secondary particle form, and therefore the positive electrode active material of Comparative Example 7 prepared using this also has a secondary particle form.
[0133] Experimental example 2: Electrochemical characterization Cathode and half-cell manufacturing Using the positive electrode active material prepared in Example 1, carbon black (DenkaBlack, manufactured by Denka Corporation) as a conductive material and PVdF (Kureha, KF1300) as a binder were added in a weight ratio of 97.5:1:1.5 (positive electrode active material:conductive material:binder) to a solvent (N-methylpyrrolidone (NMP), manufactured by Oi Chemical Industries, Ltd.) to prepare a composition for forming a positive electrode active material layer.
[0134] The prepared composition for forming a positive electrode active material layer was coated on one side of an aluminum foil current collector having a thickness of 12 μm and dried at 135° C. for 3 hours to form a positive electrode active material layer. Then, the positive electrode active material layer was rolled using a roll press method to prepare a positive electrode having a porosity of 24% in the positive electrode active material layer after rolling.
[0135] Instead of the positive electrode active material produced in Example 1, the positive electrode active materials of Examples 2 to 4 and Comparative Examples 1 to 9 were used to produce positive electrodes in the same manner as described above.
[0136] A half-cell was fabricated using the prepared positive electrode and lithium metal as the negative electrode.
[0137] Electrochemical characterization methods The coin half cell prepared above was charged at 25°C at a constant current (CC) of 0.2C up to 4.25V, then charged at a constant voltage (CV) until the charge current reached 0.05C (cut-off current), and the charge capacity was measured. After leaving it for 20 minutes, it was discharged at a constant current (CC) of 0.2C down to 2.5V, and the discharge capacity of the first cycle was measured. It was fully charged in the same manner, and a discharge current of 0.2C was applied for 10 seconds, and the initial resistance (DCIR) was measured by dividing the voltage difference between immediately before and 10 seconds after the current application by the current.
[0138] The cell that had completed the first cycle was transferred to a chamber at 45°C, and repeatedly charged and discharged at 0.33C until the 40th cycle. The discharge capacity at the 40th cycle was measured, and the discharge capacity at the 40th cycle was calculated relative to the discharge capacity at the first cycle to evaluate the capacity retention rate. In addition, at the 40th cycle, the cell was discharged to 2.5V at a constant current (CC) of 0.2C, and the change in voltage from the fully charged state until 10 seconds of discharge was divided by the current to obtain the discharge resistance (40 th DCR) and measure the initial resistance (1 st The discharge resistance at the 40th cycle was calculated against the DCR to obtain the resistance increase rate (%), which was shown as the life resistance (%).
[0139] [Table 1]
[0140] Referring to Table 1, it can be seen that the positive electrode active materials of Examples 1 to 4 exhibit uniformly excellent electrochemical properties such as high discharge capacity and capacity retention rate, and low lifetime resistance and initial resistance. Meanwhile, the positive electrode active materials of Comparative Examples 1 to 6 and 9 exhibit relatively low discharge capacity and relatively poor properties in at least one of the initial resistance, capacity retention rate and lifetime resistance. Meanwhile, it can be seen that the positive electrode active materials of Comparative Examples 7 and 8 exhibit high discharge capacity, but are not as good as those of Examples 1 to 4 in lifetime properties such as capacity retention rate and lifetime resistance.
[0141] This result is believed to be because the positive electrode active materials of Examples 1 to 4, unlike Comparative Examples 1 to 9, contain a cobalt coating located at a strong interface, and the cobalt coating located at the strong interface causes the NiO degraded layer to have an NCM structure with a relatively high cobalt concentration, thereby improving cation mixing and structural instability due to the collapse of the layered structure, etc. As a result, it was confirmed that the positive electrode active material satisfying the configuration of the present invention can solve problems such as increased resistance, decreased capacity, decreased output, and decreased life characteristics.
Claims
1. a lithium transition metal oxide in single particle form; and a coating portion including cobalt formed on the surface of the single particle lithium transition metal oxide, The lithium transition metal oxide in the form of a single particle includes an interface that is divided into a strong interface where a layer structure is broken within a crystal particle and a weak interface where a layer structure is not broken, the coating portion is formed only at the strong boundary at the boundary surface.
2. The positive electrode active material according to claim 1 , wherein the lithium transition metal oxide in single particle form contains 2 to 50 crystal grains.
3. The positive electrode active material according to claim 1 , wherein the disruption of the layered structure of the strong boundaries is a disruption of the layered structure of a NiO layer.
4. The strong boundaries show shading differences in electron backscatter diffraction (EBSD) band contrast maps and Euler maps; 2 . The cathode active material of claim 1 , wherein the weak boundary has no shading difference in an electron backscatter diffraction (EBSD) band contrast map and shows shading difference in an Euler map.
5. The positive electrode active material of claim 1 , wherein the single particle lithium transition metal oxide has the strong boundaries in an amount of 10% or more based on the total number of boundaries.
6. 2. The cathode active material of claim 1, wherein the strong boundary at which the cobalt coating layer is formed comprises a nickel cobalt manganese oxide layered structure converted from a NiO layer.
7. The cobalt coating layer formed at the strong interface is LiCoO 2 The positive electrode active material of claim 1 having a composition of:
8. 2. The positive electrode active material according to claim 1, wherein the lithium transition metal oxide is a lithium composite transition metal oxide containing nickel, cobalt, and manganese.
9. The positive electrode active material according to claim 1 , wherein the lithium transition metal oxide is a lithium composite transition metal oxide represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni x Co y M 1 z M 2 1-x-y-z O 2 In the above Chemical Formula 1, M 1 is one or more selected from the group consisting of Mn and Al, 2 is one or more selected from the group consisting of B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, S, Sr, Ta, La, and Hf, and 1.0≦a≦1.3, 0.6≦x<1.0, 0≦y≦0.4, and 0≦z≦0.
4.
10. The positive electrode active material according to claim 1 , wherein the lithium transition metal oxide is a lithium composite transition metal oxide represented by the following Chemical Formula 2: [Chemical formula 2] Li a Ni b Co c Mn d M 1 e O 2 In the above Chemical Formula 2, M 1 is one or more selected from the group consisting of Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S, and 0.9≦a≦1.1, 0.8≦b<1, 0<c<0.2, 0<d<0.2, 0≦e<0.1, and b+c+d+e=1.
11. 1) mixing lithium transition metal oxide particles in single particle form and a cobalt source; 2) heat-treating the mixture of step 1).
12. The method for producing a positive electrode active material according to claim 11, further comprising mixing an additional metal source in step 1).
13. The method for producing a positive electrode active material according to claim 11, wherein the heat treatment in step 2) is performed at 500 to 800° C.
Citation Information
Patent Citations
Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same
JP2021508161A
Non-slip Road Pavement Method
KR102190104B1
Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery including same
WO2022092922A1
System for noise alarming between floors
KR1020190094529A